Benzophenone as a cheap and effective photosensitizer for the photocatalytic synthesis of dimethyl cubane-1, 4-dicarboxylate. Issue 16 (23rd February 2023) - Prentice, Callum; Martin, Alice E.; Morrison, James; Smith, Andrew D.; Zysman-Colman, Eli
Abstract : The key intramolecular [2 + 2] photochemical cycloaddition step in the synthesis of dimethyl cubane-1, 4-dicarboxylate is performed with substoichiometric amounts of the photosensitizer benzophenone. Abstract : The key intramolecular [2 + 2] photochemical cycloaddition step in the synthesis of dimethyl cubane-1, 4-dicarboxylate is performed with substoichiometric amounts of the photosensitizer benzophenone. The reaction proceeds via a Dexter energy transfer process between the triplet excited state benzophenone and a well-known cubane precursor diene. The use of the cheap and widely available benzophenone as the photosensitizer enables lower energy light to be used than the traditional photochemical process.